Toner binder

JP2025036362APending Publication Date: 2025-03-14SANYO CHEM IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024148260
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-04
Filing Date
2024-08-30
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0007】 本発明により、画像搬送性、高温高湿下における耐熱保存性、低温定着性及び耐ホットオフセット性に優れたトナーバインダーを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036362000001
    Figure 2025036362000001
  • Figure 2025036362000002
    Figure 2025036362000002
  • Figure 2025036362000003
    Figure 2025036362000003
Patent Text Reader

Abstract

To provide a toner binder that is excellent in image conveyance property, heat-resistant storageability under a high-temperature and high-humidity, low-temperature fixability, and anti-hot offset property.SOLUTION: A toner binder of the present invention is the toner binder that contains polyester resin (A) and amorphous vinyl resin (B) obtained by polycondensation of an alcohol component (x) and a carboxylic acid component (y). The polyester resin (A) contains an aliphatic polyvalent carboxylic acid (y21) in which the number of carbons of an aliphatic hydrocarbon group is between 34 and 54 as the carboxylic acid component (y) by 5 to 40 mol% on the basis of the total molar number of the carboxylic acid component (y).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner binder. [Background technology]

[0002] In recent years, along with the promotion of miniaturization, speedup, and high image quality of electrophotographic apparatuses, there has been a strong demand for improving the low-temperature fixability of toners from the viewpoint of energy saving, that is, reducing energy consumption in the fixing process. As a means for lowering the fixing temperature of the toner, a technique for lowering the glass transition point of the binding resin (toner binder) is generally used. However, if the glass transition point is too low, the hot offset resistance is reduced, and the powder tends to aggregate (block), which reduces the storage stability of the toner. The glass transition point is a design point for the binder resin, and a toner that can be fixed at a lower temperature cannot be obtained by a method of lowering the glass transition point.

[0003] Among them, a toner composition containing a polyester-based toner binder is known that is excellent in both low-temperature fixing property and hot offset resistance (see Patent Documents 1 and 2). However, in recent years, there has been an increasing demand for heat-resistant storage stability under high temperature and high humidity conditions, and for compatibility between low-temperature fixing property and hot offset resistance (fixing temperature range), and this is still insufficient. In addition, it cannot be said that the toner has sufficient image transportability to be applied to toners for commercial printing, industrial printing, and the like, and improvements in these areas are desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-77930 A [Patent Document 2] JP 2012-98719 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a toner binder which is excellent in image transportability, heat-resistant storage stability under high temperature and high humidity conditions, low-temperature fixing property and hot offset resistance. [Means for solving the problem]

[0006] The present inventors conducted extensive research to solve these problems and arrived at the present invention. That is, the present invention provides a toner binder comprising a polyester resin (A) obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y) and an amorphous vinyl resin (B), in which the polyester resin (A) contains, as the carboxylic acid component (y), an aliphatic polyvalent carboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 in an amount of 5 to 40 mol % based on the total molar number of the carboxylic acid component (y). Effect of the Invention

[0007] The present invention can provide a toner binder that is excellent in image transportability, heat-resistant storage stability under high temperature and high humidity conditions, low-temperature fixing property, and hot offset resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below.

[0009] The toner binder of the present invention is a toner binder containing a polyester resin (A) obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y) and an amorphous vinyl resin (B). In the present invention, "amorphous" means that the DSC curve does not have a clear endothermic peak in differential scanning calorimetry (also called DSC measurement).

[0010] The polyester resin (A) in the present invention is a polyester resin obtained by polycondensation of a component containing an alcohol component (x) and a carboxylic acid component (y). The polyester resin (A) contains, as the carboxylic acid component (y), an aliphatic polyvalent carboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 in an amount of 5 to 40 mol % based on the total molar number of the carboxylic acid component (y).

[0011] Examples of the alcohol component (x) include monoalcohols (x1), diols (x2), and trihydric or higher polyols (x3). Examples of the carboxylic acid component (y) include monocarboxylic acids (y1) and polycarboxylic acids (y2). Among these, a polyester resin obtained by polycondensing a component containing a diol (x2) and a polyvalent carboxylic acid (y2) is preferred from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions. These may be used alone or in combination of two or more.

[0012] Examples of the monoalcohol (x1) include linear or branched alkyl alcohols having 1 to 30 carbon atoms (such as methanol, ethanol, isopropanol, 1-decanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, and lignoceryl alcohol). Among these monoalcohols, from the viewpoint of heat-resistant storage stability under high temperature and high humidity conditions, preferred are linear or branched alkyl alcohols having 8 to 24 carbon atoms, more preferred are linear alkyl alcohols having 8 to 24 carbon atoms, even more preferred are dodecyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol and lignoceryl alcohol, and particularly preferred are stearyl alcohol and behenyl alcohol.

[0013] Examples of the diol (x2) include linear aliphatic diols having 2 to 20 carbon atoms (ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosanediol, etc.), branched aliphatic diols, Examples of the AO having 2 to 4 carbon atoms include alicyclic diols (such as 1,2-propanediol, 1,2-butanediol, 1,2-pentanediol, and 3-methyl-1,5-pentanediol), alicyclic diols (such as hydrogenated bisphenol A, hydrogenated bisphenol F, and cyclohexanediol), and the above-mentioned (straight-chain aliphatic, branched-chain aliphatic, and alicyclic) diols to which an alkylene oxide (AO) having 2 to 4 carbon atoms (2 to 30 moles added), as well as bisphenols (such as bisphenol A, bisphenol F, and bisphenol S) to which an AO having 2 to 4 carbon atoms (2 to 30 moles added) can be mentioned. Examples of the AO having 2 to 4 carbon atoms include ethylene oxide (EO), propylene oxide (PO), and butylene oxide. Among these diols, from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions, preferred are alicyclic diols (hydrogenated bisphenol A, hydrogenated bisphenol F, cyclohexanediol, etc.) and alkylene oxide (AO) adducts having 2 to 4 carbon atoms (addition mole number: 2 to 30) of alicyclic diols, more preferred are alicyclic diols (hydrogenated bisphenol A, hydrogenated bisphenol F, cyclohexanediol, etc.), and even more preferred is hydrogenated bisphenol A.

[0014] Examples of the trihydric or higher polyol (x3) include trihydric or higher polyhydric aliphatic alcohols having 3 to 36 carbon atoms (alkane polyols and their intramolecular or intermolecular dehydration products [e.g., glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, etc.]).

[0015] The content of the diol (x2) in the alcohol component (x) is preferably 40 to 100 mol %, more preferably 60 to 100 mol %, and even more preferably 80 to 100 mol %, based on the total moles of the alcohol component (x), which is a constituent of the polyester resin (A), from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions.

[0016] The content of hydrogenated bisphenol A in the diol (x2) is preferably 80 mol % or more, and more preferably 90 mol % or more, based on the total number of moles of the diol (x2) used, from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions. The content of hydrogenated bisphenol A in the alcohol component (x) is preferably 40 to 100 mol %, more preferably 50 to 100 mol %, and even more preferably 80 to 100 mol %, based on the total moles of the alcohol component (x), which is a constituent of the polyester resin (A), from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions.

[0017] Examples of the monocarboxylic acid (y1) include unsaturated monocarboxylic acids (for example, (meth)acrylic acid ["(meth)acrylic" means acryl or methacryl], crotonic acid, isocrotonic acid, cinnamic acid, etc.), and saturated monocarboxylic acids (for example, behenic acid, stearic acid, benzoic acid, etc.). Among these monocarboxylic acids, from the viewpoint of heat-resistant storage stability under high temperature and high humidity conditions, preferred are saturated monocarboxylic acids, and more preferred are behenic acid and stearic acid.

[0018] Examples of the polycarboxylic acid (y2) include aliphatic polycarboxylic acids (y21) having an aliphatic hydrocarbon group with 34 to 54 carbon atoms, and polycarboxylic acids (y22) other than (y21). Examples of the aliphatic polyvalent carboxylic acid (y21) having 34 to 54 carbon atoms in the aliphatic hydrocarbon group include dimer acid (including compounds obtained by dimerizing unsaturated fatty acids having 18 to 28 carbon atoms, such as dimerized linoleic acid and dimerized erucic acid), trimer acid (including compounds obtained by trimerizing unsaturated fatty acids having 13 to 18 carbon atoms, such as trimerized linoleic acid), hydrogenated dimer acid ("Pripol 1009-LQ-(GD)" (dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) (manufactured by Croda)]), and hydrogenated trimer acid. Examples of the dimer acid include Tsunodyme 395 (manufactured by Tsuno Foods Industry Co., Ltd.) and Haridarimer 200 (manufactured by Harima Chemicals Co., Ltd.). In addition, Tsunodyme 216 (manufactured by Tsuno Foods Industry Co., Ltd.), which is a mixed dimer acid containing a monomer acid and a trimer acid, can be used. The number of carbon atoms in the aliphatic hydrocarbon group herein means the number of carbon atoms excluding the carbon in the carbonyl group of the carboxylic acid.

[0019] Examples of the polyvalent carboxylic acid (y22) other than (y21) include the following. Examples of dicarboxylic acids (y221) include alkanedicarboxylic acids having 2 to 34 carbon atoms (including the carbonyl group carbon) {linear alkanedicarboxylic acids (succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,18-octadecanedicarboxylic acid, etc.) and branched alkanedicarboxylic acids (decylsuccinic acid, etc.)}, alkenedicarboxylic acids having 4 to 34 carbon atoms (including the carbonyl group carbon) (dodecenylsuccinic acid, etc.), alkenylsuccinic acids such as succinic acid, pentadecenylsuccinic acid, and octadecenylsuccinic acid, maleic acid, fumaric acid, and citraconic acid), alicyclic dicarboxylic acids having 6 to 34 carbon atoms (including the carbon of the carbonyl group), and aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, t-butylisophthalic acid, 2,6-naphthalenedicarboxylic acid, and 4,4'-biphenyldicarboxylic acid, etc.). Among these dicarboxylic acids, from the viewpoint of low-temperature fixability and heat-resistant storage stability under high temperature and high humidity conditions, alkanedicarboxylic acids having 2 to 34 carbon atoms (including the carbon of the carbonyl group) are preferred, more preferably linear alkanedicarboxylic acids having 2 to 34 carbon atoms (including the carbon of the carbonyl group), and even more preferably adipic acid, sebacic acid, and dodecanedioic acid.

[0020] Examples of the trivalent or higher carboxylic acid component (y222) include aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid) and aliphatic tricarboxylic acids having 6 to 33 carbon atoms (such as hexanetricarboxylic acid). Of these trivalent or higher carboxylic acid components, trimellitic acid is preferred from the viewpoint of low-temperature fixability.

[0021] As the carboxylic acid component (y), anhydrides and lower alkyl (carbon number: 1 to 4) esters (methyl ester, ethyl ester, isopropyl ester, etc.) of these carboxylic acids may be used, or the anhydrides or lower alkyl esters may be used in combination with the above-mentioned carboxylic acids.

[0022] The polyester resin (A) contains, as the carboxylic acid component (y), an aliphatic polyvalent carboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 in an amount of 5 to 40 mol % based on the total number of moles of the carboxylic acid component (y), preferably 10 to 40 mol %, and more preferably 20 to 30 mol %. If it is less than 5 mol %, the image transportability and low-temperature fixability are deteriorated, and if it exceeds 40 mol %, the heat-resistant storage stability under high temperature and high humidity conditions is deteriorated. It is believed that the polyester resin (A) contains 5 to 40 mol % of an aliphatic polyvalent carboxylic acid (y21) having 34 to 54 carbon atoms in the aliphatic hydrocarbon group based on the total moles of the carboxylic acid component (y), so that the amorphous vinyl resin and the polyester resin are in a moderately finely dispersed state. As a result, it is believed that the image transportability, low-temperature fixability, heat resistance storage stability under high temperature and high humidity conditions, and hot offset resistance are improved.

[0023] The flow softening point of the polyester resin (A) measured with a flow tester is preferably 80° C. or more and 130° C. or less, more preferably 90° C. or more and 120° C. or less, from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions. The flow softening point (T 1 / 2 The measurement method of is described below. Using a constant test force extrusion type capillary rheometer flow tester {e.g., Shimadzu Corporation, CFT-500D}, 1 g of the measurement sample is heated at a temperature increase rate of 6°C / min. At this time, a load of 1.96 MPa is applied by the plunger, and the sample is extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. A graph of "plunger drop (flow value)" vs. "temperature" is drawn, and the temperature corresponding to half the maximum value of the plunger drop is taken as the flow softening point [T 1 / 2 〕

[0024] The flow softening point of the polyester resin (A) can be adjusted by controlling the weight average molecular weight of the polyester resin (A). Increasing the weight average molecular weight of the polyester resin (A) increases the softening point of the polyester resin (A), and decreasing the weight average molecular weight decreases the softening point of the polyester resin (A).

[0025] In the present invention, the polyester resin (A) can be produced in the same manner as known polyester resin production methods. For example, the polyester resin (A) can be produced by reacting components including an alcohol component (x) and a carboxylic acid component (y) in an inert gas (nitrogen gas, etc.) atmosphere at a reaction temperature of preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C. The reaction time is preferably 30 minutes or more, more preferably 2 to 40 hours, from the viewpoint of ensuring the polycondensation reaction. It is also effective to reduce the pressure in order to improve the reaction rate at the end of the reaction.

[0026] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxy bis(triethanol aminate), titanium dihydroxy bis(triethanol aminate), titanium monohydroxy tris(triethanol aminate), titanyl bis(triethanol aminate) and their intramolecular polycondensates, etc.}, and catalysts described in JP-A-2007-11307 (titanium tributoxy terephthalate, titanium triisopropoxy terephthalate, titanium diisopropoxy diterephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.), and zinc acetate, etc. Among the above, titanium-containing catalysts are preferred from the viewpoint of hot offset resistance and charging stability.

[0027] The reaction ratio of the alcohol component (x) and the carboxylic acid component (y), that is, the molar ratio {[OH] / [COOH]} of the hydroxyl group of the alcohol component (x) to the carboxyl group of the carboxylic acid component (y), is preferably 1 / 1 to 1.5 / 1, more preferably 1 / 1 to 1.2 / 1, further preferably 1 / 1 to 1.1 / 1, and particularly preferably 1 / 1 to 1.05 / 1. The hydroxyl group is derived from the alcohol component (x).

[0028] The peak top temperature (Tm) of the endothermic peak of the polyester resin (A) in the present invention is preferably 60 to 74° C., more preferably 66 to 73° C., from the viewpoints of low-temperature fixability and heat-resistant storage stability under high-temperature and high-humidity conditions. If it is 60° C. or higher, the heat-resistant storage stability under high-temperature and high-humidity conditions is good, and if it is 74° C. or lower, the low-temperature fixability is good.

[0029] The hydroxyl value of the polyester resin (A) of the present invention is preferably 6.0 to 40.0 mgKOH / g, more preferably 7.0 to 31.0 mgKOH / g, and even more preferably 10.0 to 25.0 mgKOH / g, from the viewpoints of charge stability and heat-resistant storage stability under high temperature and high humidity. If it is 6.0 mgKOH / g or more, charge stability is good, and if it is 40.0 mgKOH / g or less, heat-resistant storage stability under high temperature and high humidity is good.

[0030] The acid value of the polyester resin (A) in the present invention is preferably 7 to 20 mgKOH / g, more preferably 8 to 17 mgKOH / g, and further preferably 9 to 15 mgKOH / g, from the viewpoints of charge stability and heat-resistant storage stability under high temperature and high humidity conditions.

[0031] The solubility parameter (sometimes abbreviated as SP value) of the polyester resin (A) in the present invention is preferably 10.1 to 10.9 (cal / cm 3 ) 1 / 2 and more preferably 10.2 to 10.8 (cal / cm 3 ) 1 / 2 and more preferably 10.3 to 10.7 (cal / cm 3 ) 1 / 2 10.1(cal / cm 3 ) 1 / 2 If it is more than 10.9 (cal / cm), the heat resistance and preservability under high temperature and high humidity conditions will be good. 3 ) 1 / 2 If it is less than this, the low-temperature fixability is good. In the present invention, the SP value (cal / cm 3 ) 1 / 2 is a value calculated by the method described in Polymer Engineering and Science, Vol. 14, pp. 151-154, by Robert F. Fedors et al.

[0032] The SP value of the polyester resin (A) can be adjusted by the molar amount of the aliphatic polycarboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 relative to the total carboxylic acid components (y) constituting the polyester resin (A). Increasing the molar amount of the aliphatic polycarboxylic acid (y21) decreases the SP value, whereas decreasing the molar amount increases the SP value.

[0033] The number average molecular weight (Mn) of the polyester resin (A) in the present invention is preferably 1,900 to 7,700, more preferably 2,200 to 6,000, and further preferably 2,500 to 5,000.

[0034] The weight average molecular weight (Mw) of the polyester resin (A) in the present invention is preferably from 7,000 to 30,000, more preferably from 7,000 to 25,000, and further preferably from 8,000 to 20,000.

[0035] The peak top molecular weight of the polyester resin (A) in the present invention is preferably from 7,000 to 30,000, more preferably from 7,000 to 25,000, and further preferably from 8,000 to 15,000.

[0036] In the present invention, the peak top molecular weight (hereinafter sometimes abbreviated as Mp) of the polyester resin (A) and the amorphous vinyl resin (B) described below can be measured using GPC under the following conditions. The resin was dissolved in tetrahydrofuran (THF), and the resulting solution was used as a sample solution for measurement by gel permeation chromatography (GPC) under the following conditions. Equipment: HLC-8120 (Tosoh Corporation) Column: TSK GEL GMH6 x 2 (Tosoh Corporation) Measurement temperature: 40℃ Sample solution: 0.25% by weight THF solution (insoluble matter was removed by filtration using a glass filter) Solution injection volume: 100μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weights: 500, 1050, 2800, 5970, 9100, 18100, 37900, 96400, 190000, 355000, 1090000, 2890000) (manufactured by Tosoh Corporation)

[0037] The amorphous vinyl resin (B) in the present invention is a vinyl resin containing a styrene monomer as a constituent monomer. In addition to the styrene monomer, a (meth)acrylic acid ester monomer, a carboxyl group-containing vinyl monomer, a sulfonic acid group-containing vinyl monomer, a nitrile monomer, and a vinyl ester monomer can be used in combination as a constituent monomer. Among the constituent monomers, it is preferable to contain a (meth)acrylic acid ester monomer and / or a carboxyl group-containing vinyl monomer as a constituent monomer. By using a (meth)acrylic acid ester monomer and / or a carboxyl group-containing vinyl monomer in combination, it is preferable in that the glass transition temperature of the amorphous vinyl resin (B) and the compatibility with the polyester resin (A) can be easily controlled. In the present invention, "(meth)acrylic" means "acrylic" and / or "methacrylic", and "(meth)acrylo" means "acrylo" and / or "methacrylo".

[0038] Examples of the styrene monomer include styrene and alkylstyrenes having an alkyl group with 1 to 3 carbon atoms (for example, α-methylstyrene and p-methylstyrene), and each of them may be used alone or in combination of two or more. From the viewpoint of cost, styrene is preferred.

[0039] Examples of the (meth)acrylic acid ester monomer include alkyl (meth)acrylates having an alkyl group with 1 to 18 carbon atoms [e.g., methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, etc.], hydroxylalkyl (meth)acrylates having an alkyl group with 1 to 18 carbon atoms [e.g., hydroxylethyl (meth)acrylate, etc.], and alkylamino group-containing (meth)acrylates having an alkyl group with 1 to 18 carbon atoms [e.g., dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc.]. Among these (meth)acrylic acid ester monomers, from the viewpoint of storage stability, preferred are alkyl (meth)acrylates in which the alkyl group has 1 to 18 carbon atoms and mixtures of two or more kinds thereof, more preferred are alkyl (meth)acrylates in which the alkyl group has 1 to 7 carbon atoms and mixtures of two or more kinds thereof, even more preferred are alkyl (meth)acrylates in which the alkyl group has 1 to 5 carbon atoms, and particularly preferred is n-butyl acrylate.

[0040] Examples of the carboxyl group-containing vinyl monomer include monocarboxylic acids [including those having 3 to 15 carbon atoms, such as (meth)acrylic acid, crotonic acid, and cinnamic acid], dicarboxylic acids [including those having 4 to 15 carbon atoms, such as (anhydrous) maleic acid, fumaric acid, itaconic acid, and citraconic acid], and dicarboxylic acid monoesters [monoalkyl (carbon number 1 to 18) esters of the above dicarboxylic acids, such as monoalkyl maleate, monoalkyl fumarate, monoalkyl itaconic acid, and monoalkyl citraconic acid]. Of these carboxyl group-containing vinyl monomers, monocarboxylic acids are preferred from the viewpoint of charge stability, and (meth)acrylic acid is more preferred.

[0041] Examples of sulfonic acid group-containing vinyl monomers include alkene sulfonic acids having 2 to 14 carbon atoms, styrene sulfonic acid, sulfo(hydroxy)alkyl(meth)acrylates having 5 to 18 carbon atoms, sulfo(hydroxy)alkyl(meth)acrylamides having 5 to 18 carbon atoms, and alkyl (carbon number: 3 to 18)aryl sulfosuccinic acids.

[0042] The nitrile monomers include those having 3 to 20 carbon atoms, and specific examples thereof include acrylonitrile, methacrylonitrile, and cyanostyrene.

[0043] Examples of vinyl ester monomers include aliphatic vinyl esters (including those having 4 to 15 carbon atoms, such as vinyl acetate, vinyl propionate, and isopropenyl acetate) and aromatic vinyl esters (including those having 9 to 15 carbon atoms, such as methyl-4-vinyl benzoate).

[0044] The weight ratio of the styrene monomer in the constituent monomers of the amorphous polyvinyl resin (B) of the present invention is preferably 50 to 95% by weight, more preferably 60 to 90% by weight, and even more preferably 65 to 85% by weight, based on the total weight of the monomers constituting (B). When it is 95% by weight or less, compatibility with the polyester resin (A) is good, and when it is 50% by weight or more, heat-resistant storage stability under high temperature and high humidity conditions is good. The solubility parameter (SP value) of the amorphous vinyl resin (B) is 10.0 to 10.8 (cal / cm) from the viewpoint of compatibility with the polyester resin (A). 3 ) 1 / 2 It is preferable that the density is 10.2 to 10.6 (cal / cm 3 ) 1 / 2 It is more preferable that:

[0045] The amorphous vinyl resin (B) can be obtained by a known polymerization method such as solution polymerization, bulk polymerization, suspension polymerization, or emulsion polymerization using the above-mentioned styrene monomer and, if necessary, a (meth)acrylic acid ester monomer, a carboxyl group-containing vinyl monomer, a sulfonic acid group-containing vinyl monomer, a nitrile monomer, and a vinyl ester monomer, and a radical polymerization initiator. Among these polymerization methods, solution polymerization, suspension polymerization, emulsion polymerization and combinations thereof are preferred from the viewpoint of production stability.

[0046] Examples of the radical polymerization initiator include azo polymerization initiators (e.g., azobisisobutyronitrile, azobisvaleronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobiscyanovaleric acid), inorganic peroxide polymerization initiators (e.g., hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate), and organic peroxide polymerization initiators (e.g., benzoyl peroxide, di-t-butyl peroxide, t-butyl-2-ethylperoxyhexanate, t-butyl peroxybenzoate, 1,1-di-(t-butylperoxy)cyclohexane, di-t-butylperoxyhexahydrophthalate, and 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane). Of these, preferred are 2,2'-azobis(2,4-dimethylvaleronitrile), di-t-butyl peroxide, t-butyl-2-ethylperoxyhexanate, 1,1-di-(t-butylperoxy)cyclohexane, di-t-butylperoxyhexahydrophthalate and 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane. The amount of the polymerization initiator used is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, based on 100 parts by weight of the total amount of the monomers.

[0047] As the solvent for solution polymerization, cycloalkane solvents having 5 to 12 carbon atoms (cyclohexane, methylcyclohexane, etc.), aromatic solvents having 6 to 12 carbon atoms (benzene, toluene, xylene, ethylbenzene, cumene, etc.), ester solvents (ethyl acetate, butyl acetate, etc.), and ether solvents (methyl cellosolve, ethyl cellosolve, butyl cellosolve, etc.) can be used. Of these, aromatic solvents having 6 to 12 carbon atoms are preferred, and toluene, xylene and ethylbenzene are more preferred.

[0048] Furthermore, when suspension polymerization or emulsion polymerization is carried out, the polymerization can be carried out in water using an inorganic acid salt dispersant (calcium carbonate, calcium phosphate, etc.), an organic dispersant (polyvinyl alcohol, methyl cellulose, etc.), a surfactant (s) described in JP-A-2002-284881, etc.

[0049] The acid value of the amorphous vinyl resin (B) is preferably from 5.0 to 30.0 mgKOH / g, and more preferably from 10.0 to 20.0 mgKOH / g. From the viewpoint of charge stability, the toner has a toner content of preferably 5.0 mgKOH / g or more, and from the viewpoint of heat-resistant storage stability under high temperature and high humidity conditions, the toner has a toner content of preferably 30.0 mgKOH / g or less.

[0050] The glass transition temperature of the amorphous vinyl resin (B) is preferably 50°C to 70°C, more preferably 55°C to 65°C, from the viewpoints of heat-resistant storage stability under high temperature and high humidity conditions and low-temperature fixability.

[0051] The peak top molecular weight (Mp) of the amorphous vinyl resin (B) is preferably 12,000 to 50,000 from the viewpoints of low-temperature fixability and hot offset resistance.

[0052] The toner binder of the present invention is a toner binder containing a polyester resin (A) and an amorphous vinyl resin (B), and the total weight ratio of the polyester resin (A) and the amorphous vinyl resin (B) in the toner binder is preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 89% by weight or more, and most preferably 100% by weight, based on the weight of the toner binder. In other words, a toner binder consisting of a polyester resin (A) and an amorphous vinyl resin (B) is most preferred. In addition, within a range that does not impair the effects of the present invention, known binder resins for toners other than the polyester resin (A) and the amorphous vinyl resin (B) may be contained. That is, the toner binder of the present invention may contain, as a binder resin, resins such as, for example, amorphous polyester resins, crystalline vinyl resins, epoxy resins, polycarbonate resins, and polyurethane resins, and when the above resins are contained, the weight ratio of the above resins in the toner binder is preferably 50% by weight or less, more preferably 30% by weight or less, further preferably 20% by weight or less, and particularly preferably 11% by weight or less based on the weight of the toner binder.

[0053] In the toner binder of the present invention, the weight ratio of the polyester resin (A) to the amorphous vinyl resin (B) [(A):(B)] is preferably 7:93 to 50:50, and more preferably 10:90 to 30:70, from the viewpoints of image transportability, storage stability under high temperature and high humidity conditions, low temperature fixing property, and hot offset resistance.

[0054] The method for producing the toner binder is not particularly limited, and the polyester resin (A) and the amorphous vinyl resin (B) can be produced by a known kneading and grinding method or powder mixing method.

[0055] The toner of the present invention contains the toner binder of the present invention. The toner binder of the present invention is used as a toner by mixing various additives such as a colorant, a release agent, a charge control agent, a fluidizing agent, etc., as necessary. The content of the toner binder of the present invention in the toner is preferably 60 to 98% by weight based on the weight of the toner when a dye or pigment is used as the colorant, and is preferably 25 to 80% by weight based on the weight of the toner when a magnetic powder is used.

[0056] The colorant preferably contains at least one selected from the group consisting of black colorants, blue colorants, red colorants and yellow colorants. As the colorant, any dye, pigment, etc. used as a toner colorant can be used. Specific examples of the pigment include carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Solvent Yellow (21, 77, 114, etc.), Pigment Yellow (12, 14, 17, 83, etc.), India Fast Orange, Irgasin Red, Paranitoaniline Red, Toluidine Red, Solvent Red (17, 49, 128, 5, 13, 22, 48·2, etc.), Disperse Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Solvent Blue (25, 94, 60, 15·3, etc.), Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orasol Brown B, and Oil Pink OP. If necessary, magnetic powder (powders of ferromagnetic metals such as iron, cobalt and nickel, and compounds such as magnetite, hematite and ferrite) may be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 2 to 15 parts by weight, based on 100 parts by weight of the toner binder of the present invention. When a magnetic powder is used, the content of the magnetic powder is preferably 20 to 150 parts by weight, more preferably 30 to 120 parts by weight, based on 100 parts by weight of the toner binder.

[0057] Examples of the release agent include natural waxes (beeswax, carnauba wax, montan wax, etc.), petroleum waxes (paraffin wax, microcrystalline wax, petrolatum, etc.), synthetic waxes (Fischer-Tropsch wax, polyethylene wax, polypropylene wax, oxidized polyethylene wax, oxidized polypropylene wax, etc.), and synthetic ester waxes (fatty acid esters synthesized from fatty acids having 10 to 30 carbon atoms and alcohols having 10 to 30 carbon atoms, etc.), and it is preferable to contain one or more types selected from the group consisting of these release agents. The content of the release agent is preferably 0 to 30% by weight, more preferably 0.5 to 20% by weight, and even more preferably 1 to 10% by weight, based on the weight of the toner binder of the present invention.

[0058] The melting point of the release agent is preferably from 40 to 90°C, more preferably from 45 to 85°C, and particularly preferably from 50 to 80°C, from the viewpoints of low-temperature fixability and gloss.

[0059] The kinetic viscosity of the release agent at 100° C. is preferably 3 to 20 mm from the viewpoint of low-temperature fixability and gloss. 2 / s, and more preferably 4 to 19 mm 2 / s, particularly preferably 5 to 18 mm 2 / s.

[0060] The charge control agent may be either a positively charged charge control agent or a negatively charged charge control agent, and examples thereof include nigrosine dyes, triphenylmethane dyes containing tertiary amines as side chains, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing quaternary ammonium bases, metal-containing azo dyes, copper phthalocyanine dyes, salicylic acid metal salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, halogen-substituted aromatic ring-containing polymers, etc. The content of the charge control agent may be 0 to 20% by weight, preferably 0.1 to 10% by weight, more preferably 0.5 to 7.5% by weight, based on the weight of the toner binder of the present invention.

[0061] Examples of the fluidizing agent include silica, titania, alumina, fatty acid metal salts, silicone resin particles, and fluororesin particles, and two or more of them may be used in combination. From the viewpoint of the chargeability of the toner, silica is preferred. From the viewpoint of the transferability of the toner, the silica is preferably hydrophobic. The content of the fluidizing agent may be 0 to 10% by weight, preferably 0 to 5% by weight, and more preferably 0.1 to 4% by weight, based on the weight of the toner of the present invention.

[0062] The total weight of the additives may be 3 to 70% by weight, preferably 4 to 58% by weight, and more preferably 5 to 50% by weight, based on the toner weight. By keeping the composition ratio of the toner in the above range, it is possible to easily obtain a toner having good charging characteristics.

[0063] The volume average particle diameter (D50) of the toner is preferably from 1 to 15 μm, more preferably from 2 to 10 μm, and particularly preferably from 3 to 7 μm.

[0064] The method for producing the toner is not particularly limited, and the toner may be obtained by a known kneading and grinding method, a suspension polymerization method described in JP-B-10231 / 1961, JP-A-53856 / 1984, and JP-A-61842 / 1984, an emulsion polymerization method represented by a soap-free polymerization method in which a toner is produced by directly polymerizing a monomer in the presence of a water-soluble polymerization initiator that is soluble in the monomer, an interfacial polymerization method such as a microcapsule production method, an in situ polymerization method, a coacervation method, an association polymerization method in which at least one type of fine particles are aggregated to obtain a toner of a desired particle size as disclosed in JP-A-106473 / 1987 and JP-A-186253 / 1988, a dispersion polymerization method characterized by monodispersion, a dissolution suspension method in which a necessary resin is dissolved in a non-water-soluble organic solvent and then converted into a toner in water, or a method in which the toner is dispersed in carbon dioxide in a supercritical state. Among the above-mentioned manufacturing methods, the kneading and pulverizing method and the association polymerization method in which at least one kind of fine particles are aggregated to obtain a toner with a desired particle size are preferred from the viewpoints of toner particle size control and charging stability.

[0065] For example, when a toner is obtained by a kneading and pulverizing method, the components constituting the toner except for the fluidizing agent are dry-blended using a Henschel mixer, a Nauta mixer, a Banbury mixer, or the like, and then melt-kneaded using a continuous mixing device such as a twin-screw kneader, an extruder, a continuous kneader, or a three-roll mill, and then coarsely pulverized using a mill or the like, and finally, the mixture is atomized using an air flow type pulverizer or the like, and the particle size distribution is adjusted using a classifier such as an elbow jet to produce fine particles having a volume average particle size (D50) of 4 to 12 μm, and then the fluidizing agent is mixed in a mill or the like to produce the toner.

[0066] For example, when a toner is obtained by an association polymerization method in which at least one type of fine particles are aggregated to obtain a toner with a desired particle size, the toner can be produced by obtaining a dispersion of resin particles by a method including the following steps (1) to (3) and then removing the aqueous solvent. Step (1): A step of obtaining a resin particle dispersion (a resin particle dispersion (A0) of a polyester resin (A) and a resin particle dispersion (B0) of an amorphous vinyl resin (B)) and an additive dispersion (a colorant dispersion, a release agent dispersion, etc.) Step (2): A step of mixing each of the resin fine particle dispersions with an additive dispersion to aggregate the resin fine particles and form aggregates of the resin fine particles. Step (3): Fusing the aggregates to obtain fused aggregate resin particles

[0067] Examples of the dispersion medium constituting the dispersion liquid include aqueous solvents. As the aqueous solvent, any liquid containing water as an essential component can be used without limitation, and examples of the aqueous solvent that can be used include water, an aqueous solution of an organic solvent, an aqueous solution of a surfactant (s), and a mixture of two or more of these, which will be described later. In addition, in order to improve the dispersibility of the resin in the aqueous solvent, an organic solvent may be used to dissolve the resin.

[0068] Examples of the organic solvent include aromatic hydrocarbon solvents, aliphatic or alicyclic hydrocarbon solvents, halogenated solvents, ester or ester ether solvents, ether solvents, ketone solvents, alcohol solvents, amide solvents, sulfoxide solvents, heterocyclic compound solvents, and mixed solvents of two or more of these, etc. Preferred are ethyl acetate, acetone, and methyl ethyl ketone.

[0069] In order to improve the dispersibility of the resin in the aqueous solvent, a neutralizing agent may be used to neutralize the carboxyl groups of the polyester resin (A) and the amorphous vinyl resin (B). Examples of the neutralizing agent include organic compounds such as ammonia and triethylamine, and inorganic compounds such as sodium hydroxide.

[0070] The amount of the neutralizing agent used is preferably 1 to 150 mol, more preferably 5 to 100 mol, based on 100 mol of the carboxyl groups in the polyester resin (A) and the amorphous vinyl resin (B) from the viewpoint of dispersibility.

[0071] When dispersing the polyester resin (A) and the amorphous vinyl resin (B) in an aqueous solvent, a known surfactant (s) and an inorganic dispersant can be used as an emulsifier or dispersant. The use of the surfactant (s) and the inorganic dispersant is preferred because it is easier to reduce the volume average particle size of the resin microparticles.

[0072] The surfactant (s) is not particularly limited, and examples thereof include anionic surfactants (s-1), cationic surfactants (s-2), amphoteric surfactants (s-3), and nonionic surfactants (s-4), etc. The surfactant (s) may be a combination of two or more surfactants.

[0073] Examples of the anionic surfactant (s-1) include carboxylic acids or salts thereof, sulfate salts, salts of carboxymethyl compounds, sulfonates, and phosphate salts. Examples of the cationic surfactant (s-2) include quaternary ammonium salt surfactants and amine salt surfactants. Examples of the amphoteric surfactant (s-3) include carboxylate-type amphoteric surfactants, sulfate-type amphoteric surfactants, sulfonate-type amphoteric surfactants, and phosphate-type amphoteric surfactants. Examples of the nonionic surfactant (s-4) include AO addition type nonionic surfactants and polyhydric alcohol type nonionic surfactants. Specific examples of these surfactants (s) include those described in JP-A-2002-284881.

[0074] The amount of the surfactant (s) used relative to 100 parts by weight of water as the aqueous solvent is preferably 0 to 300 parts by weight, more preferably 0.001 to 10 parts by weight, and even more preferably 0.01 to 5 parts by weight.

[0075] The volume average particle diameter of the resin fine particles is preferably 0.05 to 1 μm, more preferably 0.07 to 0.5 μm, and even more preferably 0.09 to 0.3 μm, from the viewpoint of controlling the volume particle diameter and particle size distribution of the toner. The volume average particle size of the resin fine particles can be measured using a dynamic light scattering particle size distribution measuring device "SZ-100" (manufactured by Horiba, Ltd.).

[0076] From the viewpoint of controlling the volume particle size and particle size distribution of the toner, the amount of resin fine particles in 100 parts by weight of the dispersion is preferably 1 to 70 parts by weight (solid content concentration of resin fine particles in the dispersion is 1 to 70% by weight), more preferably 5 to 65 parts by weight, and even more preferably 10 to 60 parts by weight.

[0077] Step (1) will be described below. For example, a dispersion can be produced by dispersing an organic solvent solution of the components including the polyester resin (A) in an aqueous solvent, if necessary in the presence of a suitable dispersant, and then removing the organic solvent. The dispersion method is not particularly limited, but known equipment such as low-speed shear type, high-speed shear type, friction type, high-pressure jet type, and ultrasonic type can be applied. A high-speed shear type is preferred in order to make the particle size of the fine particles in the dispersion 0.05 to 1 μm. When a high-speed shear type disperser is used, the rotation speed is not particularly limited, but is preferably 1000 to 30000 rpm, and more preferably 5000 to 20000 rpm. The dispersion time is not particularly limited, but is preferably 0.1 to 5 minutes in the case of a batch method. The temperature is preferably 5 to 200°C, and more preferably 20 to 100°C. Examples of dispersion devices include batch emulsifiers such as Homogenizer (manufactured by IKA), Polytron (manufactured by Kinematica), and Homo Mixer (manufactured by PRIMIX), Ultra Visco Mill (manufactured by IMEX), Ebara Milder (manufactured by Ebara Corporation), Filmix, and Pipeline Homo Mixer (manufactured by PRIMIX), etc.

[0078] Step (2) will be described below. The method for aggregating the resin fine particles to obtain the aggregates is not particularly limited, but may include a method in which an aggregating agent is added to the dispersion liquid. The flocculant may, for example, be a metal salt of an inorganic acid (sodium chloride, magnesium chloride, calcium chloride, aluminum chloride, aluminum sulfate, calcium sulfate, ammonium sulfate, aluminum nitrate, silver nitrate, copper sulfate, or sodium carbonate).

[0079] The temperature of the dispersion in the step (2) is preferably 5 to 100°C, more preferably 20 to 100°C, from the viewpoint of controlling the volume average particle size and particle size distribution of the resin particles. In the step (2) of forming aggregates, the pH of the dispersion is preferably 2 to 10, more preferably 3 to 6, from the viewpoint of controlling the volume average particle size and particle size distribution of the resin particles.

[0080] Step (3) will be described below. In the step (3), the temperature during fusion is preferably 5 to 200° C., more preferably 30 to 100° C., from the viewpoint of shape controllability of the resulting resin particles and toner. In the step (3), the pH of the liquid during fusion of the aggregates is preferably 3 to 10, more preferably 5 to 10.

[0081] The toner using the toner binder of the present invention is fixed to a support (paper, polyester film, etc.) by a copier, printer, etc. to form a recording material. As a method for fixing to a support, a known hot roll fixing method, flash fixing method, etc. can be used.

[0082] The toner using the toner binder of the present invention can be preferably used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More preferably, it can be used for developing full-color electrostatic images or magnetic latent images.

[0083] The present specification discloses the following:

[0084] The present disclosure (1) is a toner binder containing a polyester resin (A) obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y) and an amorphous vinyl resin (B), in which the polyester resin (A) contains, as the carboxylic acid component (y), an aliphatic polyvalent carboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 in an amount of 5 to 40 mol % based on the total molar number of the carboxylic acid component (y).

[0085] The present disclosure (2) is the toner binder according to the present disclosure (1), in which the alcohol component (x) contains hydrogenated bisphenol A in an amount of 40 to 100 mol % based on the total molar amount of the alcohol component (x).

[0086] In the present disclosure (3), the solubility parameter (SP value) of the polyester resin (A) is 10.1 to 10.9 (cal / cm 3 ) 1 / 2 The toner binder according to the present disclosure (1) or (2),

[0087] The present disclosure (4) is the toner binder according to any one of the present disclosures (1) to (3), in which the flow softening point of the polyester resin (A) measured with a flow tester is 80° C. or higher and 130° C. or lower.

[0088] The present disclosure (5) is the toner binder according to any one of the present disclosures (1) to (4), wherein the weight ratio of the polyester resin (A) to the amorphous vinyl resin (B) [(A):(B)] is 7:93 to 50:50. EXAMPLES

[0089] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to these.

[0090] The physical properties of the polyester resin, the amorphous vinyl resin and the toner were measured by the following methods.

[0091] <Acid value (AV A , A.V. B )> The acid value was measured according to the method specified in JIS K0070, except that the measurement solvent was a mixed solvent of acetone, methanol, and toluene (acetone:methanol:toluene=12.5:12.5:75).

[0092] <Glass transition temperature> The measurement was performed using a differential scanning calorimeter (DSC Q20, manufactured by TA Instruments) according to the method (DSC method) specified in ASTM D3418-82. The measurement conditions for the glass transition temperature are as follows: (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35℃ for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetric curve measured in the process of (5) was analyzed to determine the glass transition temperature.

[0093] <Volume average particle size of toner (D50) (μm)> Measurements were performed using a Coulter counter [product name: Multisizer III (manufactured by Beckman Coulter, Inc.)]. First, 0.1 to 5 mL of a surfactant (alkylbenzene sulfonate) was added as a dispersant to 100 to 150 mL of an electrolyte solution, ISOTON-II (manufactured by Beckman Coulter). 2 to 20 mg of a measurement sample was then added, and the electrolyte solution in which the sample was suspended was dispersed for approximately 1 to 3 minutes using an ultrasonic disperser. The toner volume and number were measured using a 50 μm aperture with the above-mentioned measuring device, and the volume distribution and number distribution were calculated. From the distribution obtained, the volume average particle size (D50) (μm) of the toner was obtained.

[0094] <Production Example 1> [Production of Polyester Resin (A-1)] Into a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 531 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol % based on the total number of moles of (x)), 97 parts by weight of terephthalic acid (y22-1) (29.5 mol % based on the total number of moles of (y)), 49 parts by weight of isophthalic acid (y22-2) (15.0 mol % based on the total number of moles of (y)), hydrogenated dimer acid (y21-1) [(dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) "Pripol 1009-LQ-(GD)" (manufactured by Croda)] 297 parts by weight (26.2 mol% based on the total number of moles of (y)) and 1.5 parts by weight of titanium diisopropoxy bis (triethanolamine) as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230 ° C., and the reaction was carried out for 8 hours at 230 ° C. under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180 ° C., 96 parts by weight (29.3 mol% based on the total number of moles of (y)) of isophthalic acid (y21-2) was added, and the water generated was distilled off while the temperature was reduced to 220 ° C., and the reaction was further carried out under a reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value reached 10 mg KOH / g. The resin taken out was cooled to room temperature, pulverized and granulated to obtain polyester resin (A-1).

[0095] <Production Example 2> [Production of polyester resin (A-2)] In a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 677 parts by weight of bisphenol A·PO 2-mol adduct (x-2) (100.0 mol % based on the total number of moles of (x)), 261 parts by weight of terephthalic acid (y22-1) (85.5 mol % based on the total number of moles of (x)), 100 parts by weight of hydrogenated dimer acid (y21-1) (dicarboxylic acid having 34 carbon atoms in an aliphatic hydrocarbon group) "Pripol 1009-LQ-(GD)" (manufactured by Croda)] (9.6 mol % based on the total number of moles of (y)), and 1.5 parts by weight of titanium diisopropoxybis(triethanolamine) as a condensation catalyst were placed, and the water generated was distilled off while the temperature was increased under reduced pressure to 230°C, and the reaction was carried out at 230°C for 8 hours under a reduced pressure of 0.5 to 2.5 kPa. After the temperature was raised to 180°C, 17 parts by weight (4.9 mol% based on the total number of moles of (y)) of trimellitic anhydride (y22-3) was added, and the mixture was reacted at 180°C under normal pressure for 1 hour, after which the mixture was taken out. The taken out resin was cooled to room temperature, and then crushed into particles to obtain polyester resin (A-2).

[0096] <Production Example 3> [Production of polyester resin (A-3)] In a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 258 parts by weight of hydrogenated bisphenol A (x-1) (50.0 mol % based on the total number of moles of (x)), 374 parts by weight of bisphenol A·PO 2-mol adduct (x-2) (50.0 mol % based on the total number of moles of (x)), 243 parts by weight of terephthalic acid (y22-1) (79.9 mol % based on the total number of moles of (y)), hydrogenated dimer acid (y21-1) [(dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) "Pripol 160 parts by weight (15.2 mol% based on the total number of moles of (y)) of 1009-LQ-(GD) (manufactured by Croda) and 1.5 parts by weight of titanium diisopropoxybis(triethanolamine) as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230°C under reduced pressure, and the reaction was carried out at 230°C for 8 hours under reduced pressure of 0.5 to 2.5 kPa. After the temperature was increased to 180°C, 17 parts by weight (4.9 mol% based on the total number of moles of (y)) of trimellitic anhydride (y22-3) was added, and the reaction was carried out at 180°C under normal pressure for 1 hour, and then the resin was taken out. The resin taken out was cooled to room temperature, pulverized and granulated to obtain polyester resin (A-3).

[0097] <Production Example 4> [Production of polyester resin (A-4)] Into a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 485 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol % based on the total number of moles of (x)), 81 parts by weight of terephthalic acid (y22-1) (26.0 mol % based on the total number of moles of (y)), 47 parts by weight of isophthalic acid (y22-2) (15.0 mol % based on the total number of moles of (y)), hydrogenated dimer acid (y21-1) [(dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) "Pripol 1009-LQ-(GD)" (manufactured by Croda)] 378 parts by weight (35.0 mol% based on the total number of moles of (y)) and 1.5 parts by weight of titanium diisopropoxy bis (triethanolamine) as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230 ° C., and the reaction was carried out for 8 hours at 230 ° C. under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180 ° C., 75 parts by weight (24.0 mol% based on the total number of moles of (y)) of isophthalic acid (y21-2) was added, and the water generated was distilled off while the temperature was reduced to 220 ° C., and the reaction was further carried out under a reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value became 5 mg KOH / g. The resin taken out was cooled to room temperature, pulverized and granulated to obtain polyester resin (A-4).

[0098] <Production Example 5> [Production of polyester resin (A-5)] Into a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 509 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol % based on the total number of moles of (x)), 87 parts by weight of terephthalic acid (y22-1) (27.6 mol % based on the total number of moles of (y)), 47 parts by weight of isophthalic acid (y22-2) (15.0 mol % based on the total number of moles of (y)), mixed dimer acid [weight % ratio: monomer acid (y22-4) [dicarboxylic acid having 17 carbon atoms in the aliphatic hydrocarbon group] / Dimer acid (y21-2) [dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group] / trimer acid (y21-3) [dicarboxylic acid having 51 carbon atoms in the aliphatic hydrocarbon group] = 3 / 86 / 11 ["Tsunodime 216" (Tsunodime Foods Co., Ltd.)] 340 parts by weight and titanium diisopropoxybis (triethanolamine) 1.5 parts by weight as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230 ° C., and the reaction was carried out at 230 ° C. for 8 hours under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180 ° C., 83 parts by weight of isophthalic acid (y21-2) (26.4 mol% based on the total number of moles of (y)) was added, and the water generated was distilled off while the temperature was reduced to 220 ° C., and the reaction was carried out under a reduced pressure of 0.5 to 2.5 kPa, and the reaction was carried out when the acid value reached 10 mg KOH / g. The extracted resin was cooled to room temperature and then pulverized into particles to obtain a polyester resin (A-5).

[0099] <Production Example 6> [Production of polyester resin (A-6)] In a reaction vessel equipped with a cooling tube, a heating and cooling device, a thermometer, a stirrer and a nitrogen inlet tube, 535 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol% based on the total number of moles of (x)), 106 parts by weight of terephthalic acid (y22-1) (32.0 mol% based on the total number of moles of (y)), 50 parts by weight of isophthalic acid (y22-2) (15.0 mol% based on the total number of moles of (y)), 270 parts by weight of dimerized acid of erucic acid (y21-4) [(dicarboxylic acid having 42 carbon atoms in an aliphatic hydrocarbon group) "Pripol 1004" (manufactured by Croda)] (20.0 mol% based on the total number of moles of (y)), and 1.5 parts by weight of titanium diisopropoxybis(triethanolamine) as a condensation catalyst were placed, and the water generated was distilled off while the temperature was reduced to 230°C, and the reaction was carried out at 230°C for 8 hours under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180°C, 109 parts by weight of isophthalic acid (y21-2) (33.0 mol% based on the total number of moles of (y)) was added, and then the temperature was reduced to 220°C while distilling off the water generated, and the reaction was further carried out under reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value reached 10 mgKOH / g. The taken out resin was cooled to room temperature, pulverized and granulated to obtain polyester resin (A-6).

[0100] <Comparative Production Example 1> [Production of Polyester Resin (A'-1)] In a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 733 parts by weight of bisphenol A·PO 2-mol adduct (x-2) (100.0 mol% based on the total number of moles of (x)), 317 parts by weight of terephthalic acid (y-1) (95.5 mol% based on the total number of moles of (x)), and 1.5 parts by weight of titanium diisopropoxy bis(triethanolamine) as a condensation catalyst were placed, and the water generated was distilled off while the temperature was reduced to 230°C under reduced pressure, and the reaction was carried out at 230°C for 8 hours under a reduced pressure of 0.5 to 2.5 kPa. Next, after raising the temperature to 180°C, 17 parts by weight of trimellitic anhydride (y-4) (4.5 mol% based on the total number of moles of (y)) was placed, and the reaction was carried out at 180°C under normal pressure for 1 hour, and then the resin was taken out. The resin taken out was cooled to room temperature, pulverized and granulated to obtain crystalline polyester resin (A'-1).

[0101] <Comparative Production Example 2> [Production of Polyester Resin (A'-2)] Into a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 648 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol % based on the total number of moles of (x)), 159 parts by weight of terephthalic acid (y22-1) (38.8 mol % based on the total number of moles of (y)), 79 parts by weight of isophthalic acid (y22-2) (19.4 mol % based on the total number of moles of (y)), hydrogenated dimer acid (y21-1) [(dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) "Pripol 1009-LQ-(GD)" (manufactured by Croda)] 42 parts by weight (3.0 mol% based on the total number of moles of (y)) and 1.5 parts by weight of titanium diisopropoxy bis (triethanolamine) as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230 ° C., and the reaction was carried out for 8 hours at 230 ° C. under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180 ° C., 159 parts by weight (38.8 mol% based on the total number of moles of (y)) of isophthalic acid (y21-2) was added, and the water generated was distilled off while the temperature was reduced to 220 ° C., and the reaction was further carried out under a reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value reached 10 mg KOH / g. The resin taken out was cooled to room temperature, pulverized and granulated to obtain polyester resin (A'-2).

[0102] <Comparative Production Example 3> [Production of Polyester Resin (A'-3)] Into a reaction vessel equipped with a cooling tube, a heating / cooling device, a thermometer, a stirrer, and a nitrogen inlet tube, 460 parts by weight of hydrogenated bisphenol A (x-1) (100.0 mol % based on the total number of moles of (x)), 69 parts by weight of terephthalic acid (y22-1) (23.2 mol % based on the total number of moles of (y)), 34 parts by weight of isophthalic acid (y22-2) (11.6 mol % based on the total number of moles of (y)), hydrogenated dimer acid (y21-1) [(dicarboxylic acid having 34 carbon atoms in the aliphatic hydrocarbon group) "Pripol 1009-LQ-(GD)" (manufactured by Croda)] 431 parts by weight (42.0 mol% based on the total number of moles of (y)) and 1.5 parts by weight of titanium diisopropoxy bis (triethanolamine) as a condensation catalyst were added, and the water generated was distilled off while the temperature was reduced to 230 ° C., and the reaction was carried out for 8 hours at 230 ° C. under a reduced pressure of 0.5 to 2.5 kPa. Next, after cooling to 180 ° C., 69 parts by weight (23.2 mol% based on the total number of moles of (y)) of isophthalic acid (y21-2) was added, and the water generated was distilled off while the temperature was reduced to 220 ° C., and the reaction was further carried out under a reduced pressure of 0.5 to 2.5 kPa, and the resin was taken out when the acid value reached 10 mg KOH / g. The resin taken out was cooled to room temperature, pulverized and granulated to obtain polyester resin (A'-3).

[0103] The compositions and physical properties of the polyester resins (A-1) to (A-6) obtained in Production Examples 1 to 6 and the polyester resins (A'-1) to (A'-3) obtained in Comparative Production Examples 1 to 3 are shown in Table 1. The numbers in parentheses indicate the molar percentage of each component based on the total moles of the alcohol component or carboxylic acid component.

[0104] [Table 1]

[0105] <Production Example 7> [Production of amorphous vinyl resin (B-1)] 200 parts by weight of xylene was charged into an autoclave and replaced with nitrogen. After heating to 130°C in a sealed state, the pressure was released, and the temperature was raised to 140°C in a sealed state with stirring. A mixed solution of 715 parts by weight of styrene, 270 parts by weight of butyl acrylate, 15 parts by weight of acrylic acid, 1.5 parts by weight of di-t-butyl peroxide, and 100 parts by weight of xylene was dropped over 3 hours while controlling the temperature inside the autoclave to 140°C, and polymerization was carried out. After dropping, the dropping line was washed with 50 parts by weight of xylene. After maintaining the same temperature for another 1 hour, the temperature was raised to 170°C over 1 hour. The solvent was removed at 170°C for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain amorphous vinyl resin (B-1). The composition and physical properties of amorphous vinyl resin (B-1) are shown in Table 2.

[0106] [Table 2]

[0107] <Example 1> [Production of Toner (T-1)] 30 parts by weight of polyester resin (A-1) and 70 parts by weight of amorphous vinyl resin (B-1) were mixed to obtain toner binder (C-1). Next, 100 parts by weight of toner binder (C-1), 8 parts by weight of carbon black (manufactured by Mitsubishi Chemical Corporation, MA-100) as a colorant, 4 parts by weight of paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-9) as a release agent, and 1 part by weight of Aizenspiron Black (manufactured by Hodogaya Chemical Co., Ltd., T-77) as a charge control agent were added to the mixture to form a toner by the following method. First, the mixture was premixed using a Henschel mixer [FM10B, Nippon Coke & Engineering Co., Ltd.], and then mixed using a twin-screw mixer [PCM-30, Ikegai Co., Ltd.]. The mixture was then finely pulverized using an airflow type fine pulverizer [KJ-25, Kurimoto Iron Works Co., Ltd.], and classified using an elbow jet classifier [EJ-L-3(LABO) type, Matsubo Co., Ltd.] to obtain toner particles with a volume average particle size D50 of 6 μm. Next, 113 parts by weight of the toner particles were mixed with 1 part by weight of hydrophobic silica (Aerosil R972, manufactured by Nippon Aerosil Co., Ltd.) as a fluidizing agent in a sample mill to obtain a toner (T-1) containing a toner binder (C-1).

[0108] <Examples 2 to 8> [Production of Toners (T-2) to (T-8)] Toners (T-2) to (T-8) containing toner binders (C-2) to (C-8) were obtained in the same manner as in Example 1, except that 30 parts by weight of polyester resin (A-1) and 70 parts by weight of amorphous vinyl resin (B-1) were changed to the respective parts by weight of polyester resins (A-2) to (A-6) and amorphous vinyl resin (B-1) shown in Table 3.

[0109] <Comparative Examples 1 to 3> [Production of Toners (T'-1) to (T'-3)] In Example 1, 30 parts by weight of the polyester resin (A-1) was replaced with 30 parts by weight of each of the polyester resins (A'-1) to (A'-3) shown in Table 3, respectively. In the same manner as in Example 1, toners (T'-1) to (T'-3) containing toner binders (C'-1) to (C'-3) were obtained.

[0110] [Evaluation method] The methods for measuring, evaluating and judging the image transport property, storage property under high temperature and high humidity, low temperature fixing property and hot offset resistance of the obtained toner will be described below.

[0111] <Image transportability> 0.5g of toner and 20g of ferrite carrier were placed in a 50mL glass bottle, and mixed for 10 minutes at 50 rpm with a Turbula Shaker Mixer to create a two-component developer. A solid image was created on the entire surface of the paper using a commercially available monochrome copier [AR5030, manufactured by Sharp Corporation], and the image transportability created by the paper discharge roller was evaluated according to the following criteria. Under these conditions, it is preferable that the image is rated as 0 or higher.

[0112] [Evaluation Criteria] ◎: No scratches on image during transport ○: When magnified 30 times, some scratches from the image transport can be seen. △: Scratches on the image transport can be visually confirmed in some areas. ×: Scratches caused by image transport are visible throughout the entire image.

[0113] <Heat resistance under high temperature and humidity conditions> 1 g of toner and 0.013 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed in a shaker for 1 hour, the mixture was placed in a sealed container and left to stand for 48 hours in an atmosphere of 47°C and 90% relative humidity. The cohesion was measured using a powder tester, and the heat resistance storage stability under high temperature and high humidity conditions was evaluated. The lower the value in the cohesion test determined by the following method, the better the heat resistance storage stability under high temperature and high humidity conditions. Under these evaluation conditions, a value of 4% or less is preferable. Equipment: POWDER TESTER model PT-X (manufactured by Hosokawa Micron) Sieve openings: 355μm, 250μm, 150μm Vibration width: 1mm Vibration duration: 30 seconds Operation method: Set the sieves on the vibration table of the powder tester in the following order: top 355μm, middle 250μm, bottom 150μm. Place 1g of toner on the top sieve and vibrate with a vibration amplitude of 1mm for 30 seconds. Measure the weight of toner remaining on each sieve. Cohesion: Calculated from the weight of toner used for measurement and the weight of toner remaining after sieving. Cohesion degree (%)=(U / N+M / N×3 / 5+L / N×1 / 5)×100 U: weight of top row, M: weight of middle row, L: weight of bottom row, N: weight of sample (1g)

[0114] <Low temperature fixability> The printer used was a commercially available monochrome copier [AR5030, manufactured by Sharp Corporation], and the toner was applied to the paper at a density of 1.00 mg / cm 2 The unfixed image developed to be the same as above was passed through the fixing unit of a commercially available monochrome copier [SF8400A, manufactured by Sharp Corporation] at a fixing speed (circumferential speed of the heating roller) of 213 mm / sec and a heating roller temperature range of 90 to 200°C in 5°C increments. The paper used was "CopyBond SF-70NA" (75 g / m, manufactured by Sharp Corporation). 2 ) was used. Next, the fixed image was visually inspected for the presence or absence of cold offset, and the temperature at which cold offset occurs (MFT) was measured. The lower the temperature at which cold offset occurs, the better the low-temperature fixing property. Under these evaluation conditions, it is generally preferable that the MFT is 130° C. or less.

[0115] <Hot offset resistance> Using the same method as described above for low-temperature fixability, the toner was placed on the paper and the paper was passed through a soft roller at a fixing speed (circumferential speed of the heating roller) of 213 mm / sec and at heating roller temperatures ranging from 90 to 200°C in 5°C increments. Next, the presence or absence of hot offset on the fixed image was visually observed, and the temperature at which the hot offset occurred was measured. The higher the temperature at which hot offset occurs, the better the hot offset resistance. In this evaluation condition, a temperature of 180° C. or higher is preferable.

[0116] The above evaluation results are shown in Table 3.

[0117] [Table 3]

[0118] As is clear from the evaluation results in Table 3, all of the toners (T-1) to (T-8) according to Examples 1 to 8 achieved excellent results in all performance evaluations. On the other hand, the toners (T'-1) to (T'-3) according to Comparative Examples 1 to 3 were poor in some performance items. [Industrial Applicability]

[0119] The toner using the toner binder of the present invention is excellent in image transport property, heat-resistant storage property under high temperature and high humidity conditions, low-temperature fixing property and hot offset resistance, and can be suitably used as a toner binder for toner for developing electrostatic images used in electrophotography, electrostatic recording, electrostatic printing, etc. Further, it is suitable for use as an additive for paints, an additive for adhesives, particles for electronic paper, and the like.

Claims

1. The toner binder contains a polyester resin (A) obtained by polycondensing an alcohol component (x) and a carboxylic acid component (y) and an amorphous vinyl resin (B), in which the polyester resin (A) contains, as the carboxylic acid component (y), an aliphatic polyvalent carboxylic acid (y21) having an aliphatic hydrocarbon group with a carbon number of 34 to 54 in an amount of 5 to 40 mol % based on the total molar number of the carboxylic acid component (y).

2. 2. The toner binder according to claim 1, wherein the alcohol component (x) contains hydrogenated bisphenol A in an amount of 40 to 100 mol % based on the total number of moles of the alcohol component (x).

3. The solubility parameter (SP value) of the polyester resin (A) is 10.1 to 10.9 (cal / cm 3 ) 1/2 3. The toner binder according to claim 1, wherein

4. 3. The toner binder according to claim 1, wherein the flow softening point of the polyester resin (A) measured with a flow tester is 80° C. or more and 130° C. or less.

5. 3. The toner binder according to claim 1, wherein the weight ratio of the polyester resin (A) to the amorphous vinyl resin (B) [(A):(B)] is from 7:93 to 50:50.

Citation Information

Patent Citations

  • Crystalline polyester for toner

    JP2005077930A

  • Toner binder and toner composition

    JP2012098719A